2023
DOI: 10.1101/2023.01.03.522676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An effective sanitizer for fresh produce production:In situplasma activated water treatment inactivates pathogenic bacteria and maintains the quality of cucurbit fruit

Abstract: The effect of plasma activated water (PAW) generated with a dielectric barrier discharge diffusor (DBDD) system on microbial load and organoleptic quality of cucamelons was investigated and compared to the established sanitizer, sodium hypochlorite (NaOCl). Pathogenic serotypes of Escherichia coli, Salmonella enterica, and Listeria monocytogenes were inoculated onto the surface of cucamelons (6.5 log CFU g-1) and into the wash water (6 log CFU mL-1). PAW treatment involved 2 minutes in situ with water activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We have previously shown that PAW can enhance the antibiofilm activity of topical chronic wound antiseptics underscoring its clinical application 6 . We have also demonstrated PAW's ability to outcompete bleach as a fresh produce sanitiser in the context of the food industry 7 . More recently, we have generated PAW with differing gas input sources (air, argon, nitrogen and oxygen), finding PAW generated with oxygen as the most effective at eradicating E. coli biofilms that contaminate stainless-steel surfaces 5 .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…We have previously shown that PAW can enhance the antibiofilm activity of topical chronic wound antiseptics underscoring its clinical application 6 . We have also demonstrated PAW's ability to outcompete bleach as a fresh produce sanitiser in the context of the food industry 7 . More recently, we have generated PAW with differing gas input sources (air, argon, nitrogen and oxygen), finding PAW generated with oxygen as the most effective at eradicating E. coli biofilms that contaminate stainless-steel surfaces 5 .…”
Section: Introductionmentioning
confidence: 79%
“…PAW contains various RONS crucial for its antimicrobial effectiveness against bacteria such as E. coli, S. aureus and Listeria monocytogenes [5][6][7] . PAW, produced with different gas sources, yields diverse RONS 4,5 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much higher whiteness values were observed in NaClO‐treated samples compared to that in CS–SA. This might due to the bleaching and antioxidant capacity induced by the oxidation of hypochlorite (ClO − ) in NaClO solution (Rothwell Joanna et al, 2023). Furthermore, the interference of coating film color (brown) might cause the lower whiteness values in samples compared to that in NaClO.…”
Section: Resultsmentioning
confidence: 99%